Effects of Home Environment on the Academic Performance of Elementary Grade Pupils - Naval, Jolina May (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effects of the home environment on the academic performance of elementary grade pupils in selected public elementary schools in the Binangonan District, Division of Rizal, during the School Year 2025–2026. Utilizing a descriptive survey research design, the study involved 154 teachers and 333 parents as respondents. A researcher-made questionnaire-checklist was employed to assess the perceived extent of home environment influences on pupils’ knowledge competencies, skills competencies, and submission of assigned tasks. Documentary analysis of pupils’ first-quarter grades was also conducted to determine academic performance.Findings revealed that both teachers and parents generally agreed that the home environment often affects pupils’ academic performance across the three measured domains. However, while no significant difference was found in their perceptions regarding skills competencies, significant differences existed in knowledge competencies and submission of assigned tasks. The results further indicated that most demographic variables of teachers and parents did not significantly influence their perceptions, except for selected factors such as teachers’ civil status, educational attainment, and professional experience, as well as parents’ educational attainment, occupation, and family size.The pupils’ academic performance was found to be at a satisfactory level, with a mean grade of 82.87. Moreover, a significant relationship was established between the home environment and pupils’ academic performance, suggesting that supportive and structured home conditions contribute positively to learning outcomes.The study concludes that while teachers and parents share common views in certain aspects, variations in perceptions highlight the need for strengthened collaboration. It recommends the implementation of parent education programs, enhanced teacher training, and school-based interventions to foster a supportive home learning environment and improve pupils’ academic achievement.
Keywords: home environment, academic performance, elementary pupils, parental involvement, teacher perception, descriptive research,